2005
DOI: 10.1017/s0265021503001431
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal application of bupivacaine plus morphine for pain relief after laparoscopic cholecystectomy

Abstract: In patients undergoing laparoscopic cholecystectomy, the intraperitoneal administration of morphine plus bupivacaine 0.25% reduced the analgesic requirements during the first 6 postoperative hours compared with the control group. However, the combination of intraperitoneal bupivacaine 0.25% and i.v. morphine was more effective for treatment of pain after laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Previous studies agree that postoperative pain from laparoscopy consists of three components, visceral, parietal, and referred shoulder pain distinguishing from each other in the intensity, latency, and duration. [2]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies agree that postoperative pain from laparoscopy consists of three components, visceral, parietal, and referred shoulder pain distinguishing from each other in the intensity, latency, and duration. [2]…”
Section: Discussionmentioning
confidence: 99%
“…Visceral pain has its maximum intensity during the first hour and is exacerbated by coughing, respiratory movements, and mobilization. [2]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Pain after laparoscopic cholecystectomy is affect by several factors including patient demographics, nature of underlying disease, surgical factors, volume of residual gas, type of gas used for pneumoperitoneum, and the pressure created by the pneumoperitoneum. [1318] A number of techniques have been described for reducing postlaparoscopy pain including: Preincisional infiltration and intraperitoneal instillation of levobupivacaine 0.25%;[19] intraperitoneal ropivacaine and a gas drain;[20] intraperitoneal levobupivacaine with epinephrine;[21] intraperitoneal application of bupivacaine plus morphine;[22] preincisional injection of bupivacaine;[23] pre-emptive intraperitoneal injection of ropivacaine;[24] and intraperitoneal lidocaine combined with intravenous or intraperitoneal tenoxicam. [25] It is suggested that post-laparoscopic cholecystectomy pain is multifactorial and methods for short term analgesia cannot improve postoperative functions or shortened hospitalization.…”
Section: Discussionmentioning
confidence: 99%